Faktor-faktor yang mempengaruhi Persediaan : Barang dagang, Bahan Baku, Profitabilitas, Likuiditas, Metode FIFO, Modal Kerja (Literature Review Manajemen Keuangan ) - Raisa Raisa; Nada Salsabila; Fitriana Fitriana; Sabilah Ayu Adinda Yani; Tri Yulaeli (Institut Nalanda, 2023)
Previous research or relevant research is very important in a research or scientific article. Previous research or relevant research serves to strengthen the theory and phenomena of the relationship or influence between variables. This article reviews the factors that influence inventory, namely: Merchandise, Raw Materials and Finished Goods, a study of the Financial Management literature. The purpose of writing this article is to build a hypothesis on the influence between variables to be used in further research. The results of this literature review article are: 1) Merchandise has an effect on Inventory 2) Raw Materials has an effect on Inventory and 3) Profitability has an effect on Inventory 4) Liquidity has an effect on Inventory 5) The FIFO method has an effect on Inventory 6) Working Capital has an effect on Inventory.